Evaluating the effectiveness of perceptual treatments on sharp curves: a driving simulator study. (25th November 2019) - Calvi, Alessandro; D'Amico, Fabrizio; Bianchini Ciampoli, Luca; Ferrante, Chiara
Abstract: Objective: Speed has been identified as a key risk factor in road crashes, influencing the occurrence of a road crash and its severity. Excessive speeding is particularly dangerous on highway curves, and under critical traffic and environmental conditions. Various measures have been identified to be effective in managing and controlling vehicle speed. Among these, low-cost perceptual measures have been considered to be effective tools, as they generally increase the risks perceived by drivers, or alter speed perception, and consequently lead the drivers to reduce their speeds. The overall aim of this study is 1) to investigate the effectiveness of a set of perceptual treatments in reducing the driver's speed along a sharp curve of an existing rural road that is characterized by high crash rates, and 2) to identify the most effective measure(s) to implement in the field to counteract the problem of speeding. Methods: A driving simulator study was developed and four speed-reducing measures (white and red peripheral transverse bars (PTB), optical speed bars (OSB) and chevrons) were tested on a sample of forty-two drivers. The driving speeds recorded using the treatments tests were compared to a baseline condition (treatments were not applied). Subjective measures were also collected; these included the driver's evaluation of the desired speed, risk perception, road legibility, and markings comprehension, as based on screenshot pictures that represented the simulated configurations of the treatments. Results: The outcomes demonstrated an overall effectiveness of the perceptual treatments. Particularly, red PTB were associated with a speed-reduction of up to 12 km/h along the curve under study. An analysis of the questionnaires revealed that drivers did not fully comprehend the relevant message of PTB. Despite that, the drivers did unconsciously reduce their speeds; this confirms the effectiveness of such perceptual treatments based on the optical illusion that entices drivers to reduce their speeds. Conclusions: The findings demonstrated the effectiveness of the perceptual treatments, especially red PTB, in enticing drivers to reduce their speeds whilst approaching the sharp curve under study or driving through the curve.